Optimization of Teaching Profession Courses Through Project Methods: Impact on Biology Education Students - Novallyan, Devie; Nehru (Yayasan Nurul Yakin Bunga Tanjung, 2025)
This mixed-methods quasi-experimental study examines the impact of Project-Based Learning (PjBL) on enhancing pedagogical competencies among pre-service biology teachers (N = 60) in a Teaching Profession Course. Grounded in the TPACK framework and constructive alignment theory, the research compares PjBL implementation with conventional instruction through cognitive assessments (α = 0.87), lesson plan evaluations (κ = 0.82), motivation scales, and qualitative analysis of reflective journals and project artifacts. Quantitative results demonstrate significant improvements in the PjBL group, including superior cognitive gains (p < 0.01, d = 0.82), enhanced pedagogical design skills (p = 0.013, η² = 0.28), and increased motivation (Δ23%, p<0.001). MANOVA reveals multidimensional competency development across learning, application, and self-efficacy domains (F = 9.67–14.32). Qualitative findings highlight the successful development of context-responsive STEM modules, though challenges in time management emerged. The study provides empirical evidence for PjBL's efficacy in preparing biology educators for 21st-century challenges, offering a validated model for integrating disciplinary core ideas with pedagogical praxis. These findings advocate for curriculum reforms that incorporate scaffolded PBL experiences to bridge the theory-practice gap in teacher education.